Advances in Management of Voice and Swallowing Disorders - Speyer, Renée (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Special Issue "Advances in Management of Voice and Swallowing Disorders" is dedicated to innovations in screening and assessment and the effectiveness of interventions in both dysphonia and dysphagia. In contemporary practice, novel techniques have been introduced in diagnostics and rehabilitative interventions (e.g., machine learning, electrical stimulation). Similarly, advancements in methodological approaches to validate measures have been introduced (e.g., item response theory using Rasch analysis), prompting the need to develop new, robust measures for use in clinics and intervention studies. Against this backdrop, this Special Issue focuses on studies aiming to improve early diagnostics of laryngological disorders and its management. This issue also welcomes the submission of studies on diagnostic accuracy and psychometrics performance of existing and newly developed measures. This includes but is not limited to studies investigating screening tools with sound diagnostic accuracy and robust psychometric properties. Furthermore, interventions with high levels of evidence in relation to clinical outcome using robust methodology (e.g., sophisticated meta-analytic approaches) are of great interest. This issue provides an overview of the latest advances in voice and swallowing disorders.